Damage mechanism of inner heat shield of sapphire single crystal furnace - LIAO Bin-bin (Fenmo yejin jishu)
The relationships of the evaporation rate, the saturated vapor pressure, and the working temperature of Mo in vacuum environment were investigated, and the damage mechanism of Mo inner heat shield in sapphire single crystal furnace was discussed. In the results, the core operating temperature of the sapphire single crystal furnace is above 2100 ℃, the high temperature period of each cycle is more than 120 h, and the inner heat shield evaporates in the high vacuum environment. It can be seen from the microstructure that the surface of Mo sheet is loose and porous, and the sheet thickness gradually becomes thin and peels off, losing the heat insulation effect. The formula of the thickness change due to the metal evaporation is deduced from the evaporation rate, the saturated vapor pressure, and the working time at high temperatures. The thickness change trend on the inner heat shield of sapphire single crystal furnace calculated by the formula coincides with the actual service life. Since the melting point of W metal is higher than that of Mo metal, it will hardly evaporate and become thinner under the most severe working conditions in the sapphire crystal furnace according to the calculation results by the formula. Therefore, W is an ideal substitute of the inner heat shield.